(untitled) (Journal of Imam Al-Kadhim College, 2024)
The research aims to identify the factors influencing the reduction of the phenomenon of misinformation on social media platforms, understand the tools that contribute to reducing the phenomenon of misinformation on social media platforms, determine the role and impact of relevant entities in combating the phenomenon of misinformation on social media platforms, and understand the role of education and media awareness in reducing the spread of misinformation on social media platforms. The researcher relied on a qualitative approach in this study through in-depth interviews with experts and specialists in the field of study, totaling (8) experts and specialists. To answer the research questions, the researcher arrived at the following results: One of the factors influencing the reduction of misinformation on social media platforms is raising awareness among users about the risks of misinformation and its impact on society, educating them on how to recognize fake and misleading news, and encouraging users to develop their skills in evaluating content and verifying information before sharing or relying on it. It also recommends the need to enhance awareness of the dangers of misinformation and its negative impact on society and individuals, which can be achieved through awareness campaigns on social media platforms and other media outlets. Social media platforms should adopt stricter policies to verify the accuracy of published content and combat false and misleading information